Enhancing informed consent in oncological surgery through digital platforms and artificial intelligence - Boddy, Alex (Clinical Surgical Oncology, 2025)
Informed consent is a cornerstone of ethical medical practice, particularly in high-stakes oncological surgery where treatment options are complex and risks are significant. This paper explores the potential of digital platforms and artificial intelligence (AI) to enhance the informed consent process. The traditional consent process, reliant on face-to-face interactions and paper-based documentation, is increasingly being supplemented by digital solutions that offer remote consultations, personalized patient information, and electronic consent forms. These digital pathways not only improve accessibility and patient comprehension but also streamline documentation, reducing errors and administrative burdens. AI technologies, including ambient digital scribes and large language models (LLMs), could further augment this process by generating personalized risk assessments, simplifying complex medical information, and facilitating multilingual communication. However, success will also depend on addressing ethical concerns, ensuring equitable access, and preserving the irreplaceable human connection between patients and clinicians. By augmenting rather than replacing clinician expertise, digital platforms and AI can empower patients to make truly informed decisions in oncological care.